O futebol profissional em Mato Grosso : da gênese à Copa do Mundo de 2014 - Benitez, Allan Kardec Pinto Acosta (2019)
The main topic that substantiates the debate developed in this study referers to the analysis course of the professional soccer in tbe state of mt through a historical and socialogical research in order to reveal more than a hundred years (100) of this sport in our state, from the beginnings to nowadays. The main goal of this thesis was to analyze the course of the professional soccer in Mato Grosso, since the beginnings until the present days, correlating with the state economic growth. The problem of investigation was based on the relationship between the professional soccer development and the economic growth in the state of MT. The highlight that guided the investigation was: Why the professional soccer in MT didn't keep up with the economic growth in the state? The research that substantiates the present thesis used qualitatives research techniques such as interviews and document analysis. The interview thechnique was important in our investigation because allowed us to reveal the agents‘s perception about the soccer in MT. The fourteen (14) interviews were conducted involving jornalists, soccer leaders, former players, soccer fans, public agents and others. The theoretical framework of the thesis is based on the sport sociology, in the contemporary sociological theory, in the career's sociology and in the sociological literature about soccer. Therefore we can conclude that the heterogeneity of the interests and the political and economic projects of the economic elites of the state didn't make soccer a priority project. For this reason there are so few companies in MT that sponsor local soccer teams and, consequently, there is an economic weakening of these teams, what is a big problem in the soccer business nowadays. So we confirm that there is indeed a total dissociation between the economic and productive classes and the soccer. Because of this, there is a lack of investments in the local soccer, so, there isn't support from these economic groups for the soccer in MT, except for the Cuiabá and Luverdense Teams. The Mato Grosso professional soccer is part of a peripheral space in the brazilian soccer business, as a result of the incipient professionalization and modernization of the teams, the small amout of television' s financial participation in the teams' incomes, the lack of investments from the local business in the soccer, the precarious situation of the teams basis category and the ―brown amateurismǁ that predominates in the amateur soccer in the state.